Saliva/serum ghrelin, obestatin and homocysteine levels in patients with ischaemic heart disease - Kilic, Nermin (Cardiovasc J Afr, 2017)
BACKGROUND: We aimed to compare ghrelin, obestatin, homocysteine (Hcy), vitamin B(12) and folate levels in the serum and saliva of ischaemic heart disease patients. METHODS: Serum and saliva were collected from 33 ischaemic heart disease (IHD) patients and 28 age- and body mass index-matched healthy individuals. Levels of acylated and desacylated ghrelin, obestatin and Hcy were determined using the ELISA method. RESULTS: Acylated ghrelin, desacylated ghrelin and obestatin levels in the saliva were found to be higher than those in the serum of the control group, while acylated and desacylated ghrelin levels in the saliva were significantly lower than those in the serum. Obestatin levels were higher in IHD patients (p = 0.001). Saliva and serum vitamin B12 and folate levels in IHD patients were significantly lower than in the control group (p = 0.001). CONCLUSIONS: It was determined that serum ghrelin levels increased in ischaemic heart disease patients, while serum levels of obestatin decreased.